Elevation of serum uric acid and incidence of type 2 diabetes: AÂ systematic review and meta-analysis - Yi-Li Xu; Kuan-Feng Xu; Jian-Ling Bai; Yun Liu; Rong-Bin Yu; Chun-Lan Liu; Chong Shen; Xiao-Hong Wu (Chronic Diseases and Translational Medicine, 2016)
Objective: Recently, several cohort studies suggested a positive relationship between serum uric acid (SUA) and type 2 diabetes mellitus (T2DM), which is inconsistent with the results of functional research. Our aim was to further evaluate this correlation by conducting a systematic review. Methods: Computerized literature searches of the Medline database, EMBASE database, and PubMed were used to evaluate the relationship between SUA and T2DM in cohort studies. Cochran's Q and I2 statistics were used to evaluate heterogeneity among studies, and pooled relative risk (RR) and odds ratio (OR) with 95% confidence intervals (CIs) were calculated using random-effects and fixed-effects models. The summary RR and OR of per 1Â mg/ml-SUA increase were calculated separately because of their different epidemiological implications and calculation methods. Additionally, sensitivity analysis, stratified analysis, meta-regression, and multiple meta-regression were applied to investigate the heterogeneity among studies. Results: A total of 970 articles were retrieved from the searches. Sixteen publications of cohort studies containing 61,714 participants were included. The pooled RR was 1.131 (95% CI: 1.084â1.179) with significant heterogeneity among studies (I2Â =Â 51.9%, PÂ =Â 0.018). Adjusted RR to evaluate the stability of the relationship between SUA and T2DM in the sensitivity analysis was similar (RRÂ =Â 1.140, 95% CI:Â 1.087â1.197), with statistically significant heterogeneity (I2Â =Â 54.5%, PÂ =Â 0.015). Stratified analysis and meta-regression showed that the positive relationship remained irrespective of age, sex, region, and adjustment for confounding factors including body mass index, fasting blood glucose, systolic blood pressure, diastolic blood pressure, alcohol consumption, smoking, blood cholesterol, waist circumference, fatty liver, and drugs affecting SUA. Conclusion: Although SUA is independently associated with development of T2DM, insulin resistance increased as the baseline SUA concentration increased; thus, the correlation between SUA and T2DM requires further evaluation and the baseline insulin resistance status should also be considered. Keywords: Uric acid, Diabetes, Meta-analysis